Collaboration Model Between Local Government and Community Protection Unit in The Development of Kuta Mandalika Tourism in Central Lombok Regency, West Nusa Tenggara Province - Aprimawati, Baiq; Pujayanti, Luh Putu Vera Astri; Taufik, Muhamad Zaki (Socious Journal, 2025)
This study aims to analyze and formulate a collaboration model between the Regional Government and the Community Protection Unit (Satlinmas) in developing the Kuta Mandalika tourist destination in Central Lombok Regency, West Nusa Tenggara Province. This study uses the collaborative theoretical framework of Ansell and Gash (2008) which emphasizes face-to-face dialogue, trust-building, and shared commitment, as well as the Pentahelix approach involving five main actors: government, academics, the business world, communities, and the media. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participant observation, and documentation studies. The results show that collaboration between the regional government and Satlinmas is still sectoral and has not been optimally integrated within the Pentahelix framework. Several inhibiting factors such as lack of institutional capacity, the absence of specific regulations governing the role of Satlinmas in the tourism sector, and weak cross-sectoral coordination are the main challenges. Therefore, this study recommends strengthening regulatory-based collaborative mechanisms, training the capacity of Satlinmas in tourism services, and establishing a cross-actor communication forum as a form of real implementation of Ansell and Gash's theory and the Pentahelix approach in developing sustainable tourism in the Mandalika area.